The Effect Of Beetroot Juice (Beta Vulgaris L) And Star Fruit (Averrhoa Carambola L) On The Reduction Of Blood Pressure In Second Trimester Pregnant Women With Gestational Hypertension - Retnaningsih, Reny; Wijayanti, Tut Rayani Aksohini (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Background: Gestational hypertension is usually defined as high bloodpressure that develops after 20 weeks of gestation in the absence ofproteinuria. Beets and star fruit contain vitamins and minerals such as Bvitamins and calcium, potassium, phosphorus, and iron, which can safelylower blood pressure in pregnancy.Objective: Determine the effect ofbeetroot juice (Beta vulgaris L) and star fruit (Averrhoacarambola L) on reducing blood pressure in pregnant women in the second trimester with gestational hypertension.Method: This pre-experimental research was a one-group pretest-posttest design with 200 ml/day of beet and starfruit juiceintervention for two weeks. The samples taken were 15 second trimesterpregnant women with gestational hypertension.The data taken is bloodpressure before and after treatment—data analysis using paired t-test.Results: data onthe mean systolic blood pressure before treatment is 146.53mmHg and after treatment is 126.07 mmHg and the average diastolic blood pressure before treatment is 94.53 mmHg and after treatment is 91.13mmHg. There is an effect of beet and star fruit juice administration onsystolic and diastolic blood pressure in second-trimester pregnant womenwith gestational hypertension (p 0.05).Conclusion : pregnant women withgestational hypertension is to treat hypertension using beet and starfruit juice so that hypertension can be treated immediately.Keywords: Beetroot Juice, Beta vulgaris L , Star Fruit , Averrhoa carambola L, Gestational Hypertension